Interpolyation In Smoothing Tin Model Of The Earth - Xamrabayeva N.A ,Avazbayev S, Muslimova P.SH, Abduqodirova S.N (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article deals with engineering (strategic site construction, buildings and structures, material cultural heritage sites), project (underground and overhead pipelines, railways, roads, power lines, fields and minerals, irrigation networks, hydraulic structures). Improved interpolation techniques for determining the most commonly used measuring heights in the process of land surveying, solving engineering problems on topographic maps and surveying land cadastral works (agriculture, fisheries) and the state cadaster illuminated. In addition, design of linear, dotted and field-themed objects, the study of absolute heights for volume measurements, the analysis of survey results in software for the geo-information system, the mapping of Earth's dimensions, the determination of unknown altitude and land grinding. Optimized using an improved formula for implementation. In addition, there is a section with a relief section height within each relief interval, and traditional methods used to determine intermediate values ??have caused discomfort to specialists or users of this formula. In this paper, it is widely used that the formula developed can be used to develop a high-precision study of the absolute value of an unknown height and to develop a sequence algorithm for the implementation of modulation systems in the geo-information system family software.